EFFECTIVE NON-PHARMACOLOGICAL STRATEGIES FOR PAIN RELIEF IN CHILDBIRTH (Fiep Bulletin - online, 2014)
Clinical quantitative trial of therapeutic intervention type that aimed to evaluate, "before and after", the effectiveness of non-pharmacological strategies for relieve the pain intensity of women in the active phase of childbirth labor. The study was developed in a public maternity in the city of Natal/RN, in Northeast region of Brazil, and had as a sample, 100 considered low-risk women. To evaluate the pain intensity during childbirth, used the visual analogue scale for measurement. After the application of non-pharmacological strategies (breathing exercises, muscle relaxation and lumbosacral massage), the women of the study felt significant relief (ñ
Keywords: Labor; pain relief; Women's Health